Pengetahuan Mahasiswa Pendidikan Guru Sekolah Dasar dalam Merepresentasikan Operasi Pecahan dengan Model Persegi Panjang - Zetra Hainul Putra (Universitas Hamzanwadi, 2016)
This study aims to investigate pre-service elementary teachers’ knowledge on representing fraction operations by rectangle models. The subjects of this study are 64 pre-service elementary teachers from elementary school techer training study program, faculty of teacher training and education, University of Riau. The research method used is quantitative descriptive by giving a test related to the representations of fraction operations by rectangle models. The result shows that 82,81% pre-service elementary teachers were success representing addition of fractions, and 67,19% of them for subtraction of fractions. Meanwhile, 44,53% pre-service elementary teachers were success representing multiplication of fractions and 24,22% of them for divison of fractions. Then, they were still get difficulty in representing multiplication and division of fractions using rectangle models than addition and subtraction of fractions.